Carbon catalyst from palm kernel shell (PKS) for methane cracking : Effect of preparation - Nur Fathin Syuhada, Hazman; Muhammad Syafiq, Mat Zaki; Asmida, Ideris (Elsevier Ltd, 2023)
The effect of preparation on the performance of carbon catalyst derived from palm kernel shell (PKS) in methane cracking was evaluated. The PKS-carbon catalysts were prepared via pyrolysis at different temperatures (550, 650, 750 °C) and for different pyrolysis times (30, 60, 100 min) and their catalytic performance in methane cracking was analysed in a fixed bed reactor. The BET surface area of the PKS-carbon catalyst increased from 40.7 to 43.0 m2/g as the pyrolysis temperature increased from 550 to 650 °C, but decreased to 24.1 m2/g at 750 °C. During methane cracking, the PKS-carbon catalyst prepared at 650 °C demonstrated 30 % initial CH4 conversion and gave the highest initial H2 yield of up to 88 %. This indicates that pyrolysis temperature influences the carbon catalyst's surface area, and a higher surface area promotes better initial catalytic activity in methane cracking. In addition, the PKS-carbon catalyst prepared for longer pyrolysis time (100 min) contained more desirable surface oxygen-containing functional groups (–OH, C=O, –COOH) than the ones prepared for 30 and 60 min. Therefore, the PKS-carbon catalyst pyrolyzed for 100 min exhibited 35 % initial CH4 conversion and the highest initial H2 yield of 95 %. This suggests that a longer pyrolysis time produces more desirable surface oxygen-containing functional groups, which enhance reactant activation in methane cracking. In conclusion, the preparation of PKS-carbon catalyst influences the surface area and surface oxygen- containing functional groups, which affect the catalyst's performance in methane cracking.